Outcomes of Physician-Modified Endografts for Juxtarenal and Pararenal Abdominal Aortic Aneurysms: A Systematic Review and Single-Arm Meta-Analysis - Haoran Wang; Mohammed Al-Falahi; Bernhard Hruschka; Panagiotis Doukas; Christian Uhl; Jelle Frankort; Alexander Gombert (Journal of Clinical Medicine, 2026)
Background: To present perioperative and follow-up outcomes of physician-modified endograft (PMEG) repair for juxtarenal and pararenal abdominal aortic aneurysms. Methods: This PRISMA 2020 systematic review and single-arm meta-analysis was registered with PROSPERO (CRD420261340339). PubMed, Embase, Web of Science, the Cochrane Library, and ClinicalTrials.gov were searched until December 2025. Eligible reports described full-text-confirmed cohorts of at least five patients treated with PMEG. The strict primary analysis required endpoint-separable juxtarenal or pararenal populations and used random-effects generalized linear mixed models for pooled proportions. Methodological quality and evidence certainty were assessed using the Joanna Briggs Institute checklist and GRADE framework. Results: Fifteen eligible reports described 981 patients before overlap adjudication; 10 reports originated from one institution and contained overlapping populations. After pathology and endpoint-level overlap adjudication, one to four independent populations informed each endpoint estimate, and single-source outcomes were not pooled. Technical success was 97.8% (95% CI, 94.8–99.1%; three populations, 228 patients), and 30-day mortality was 2.3% (95% CI, 1.1–4.8%; four populations, 299 patients). Acute kidney injury, stroke, and spinal cord ischemia occurred in 4.5%, 1.6%, and 1.7% of patients, respectively. During available follow-up, the single-source Type III endoleak estimate was 3.4% (7/203), any reintervention was 13.2% (95% CI, 2.9–43.7%; two populations, 217 patients; I2 = 89.0%), and patient-level target-vessel occlusion was 2.4% (95% CI, 0.6–9.1%; 2 populations, 83 patients). Follow-up estimates were exploratory report-period proportions. GRADE certainty was very low for all key outcomes. Conclusions: PMEG repair demonstrated a high technical-feasibility signal and low observed early event rates in experienced centers, but clinical effectiveness and durability remain uncertain. The evidence base is dominated by overlapping expert-center reports and should not be interpreted as establishing equivalence or superiority to custom-manufactured FEVAR.